2021
DOI: 10.3906/sag-2009-98
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of the effects of propofol/ketamine versus propofol/fentanyl on nausea- vomiting administered for sedation in children undergoing magnetic resonance imaging: a prospective randomized double-blinded study

Abstract: Background/aim: In this study, we aimed to compare the effects of propofol-ketamine and propofol-fentanyl sedations on post-procedure nausea-vomiting in children undergoing magnetic resonance imaging (MRI). Materials and methods:This study included 100 pediatric patients (2-10 years old) who had propofol-ketamine and propofol-fentanyl for sedation to undergo MRI. The patients were divided into two groups, and sedation was performed through propofolketamine (Group K; n=50) or propofol-fentanyl (Group F; n=50). … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(9 citation statements)
references
References 21 publications
0
9
0
Order By: Relevance
“…[ 15 ] found that the discharge time was almost twice the recovery time, whereas, in our study, the mean recovery time ( P > 0.05) and the discharge time ( P > 0.05) were comparable between both the groups, as it could be explained by the low rates of propofol infusion (75 and 100 µg/kg/min). Adverse effects like nausea and vomiting were seen more with the propofol–ketamine combination[ 15 16 ], but in our study, none of the patients in either group had postprocedure vomiting. Better quality of images was obtained with Group KP.…”
Section: Discussionmentioning
confidence: 55%
“…[ 15 ] found that the discharge time was almost twice the recovery time, whereas, in our study, the mean recovery time ( P > 0.05) and the discharge time ( P > 0.05) were comparable between both the groups, as it could be explained by the low rates of propofol infusion (75 and 100 µg/kg/min). Adverse effects like nausea and vomiting were seen more with the propofol–ketamine combination[ 15 16 ], but in our study, none of the patients in either group had postprocedure vomiting. Better quality of images was obtained with Group KP.…”
Section: Discussionmentioning
confidence: 55%
“…Studies have shown that combining ketamine at doses of 0.5–1 mg/kg anesthesia applied in pediatric magnetic resonance imaging and laparoscopic cholecystectomy in adults could increase the incidence of PONV. 32 , 33 Nevertheless, adjuvant fentanyl with ketamine at 0.3 mg/kg for self‐controlled intravenous analgesia after thoracic spine surgery did not increase the incidence of PONV. 34 So, it could be thought that S‐ketamine at the dose of 0.2–0.3 mg/kg was not considered sufficient to increase the incidence of nausea and vomiting.…”
Section: Discussionmentioning
confidence: 91%
“…PONV effects of S‐ketamine are considered dose‐dependent like those triggered by ketamine. Studies have shown that combining ketamine at doses of 0.5–1 mg/kg anesthesia applied in pediatric magnetic resonance imaging and laparoscopic cholecystectomy in adults could increase the incidence of PONV 32,33 . Nevertheless, adjuvant fentanyl with ketamine at 0.3 mg/kg for self‐controlled intravenous analgesia after thoracic spine surgery did not increase the incidence of PONV 34 .…”
Section: Discussionmentioning
confidence: 99%
“…The commonly used anesthesia methods are propofol plus low-dose fentanyl intravenous analgesia and intravenous combined inhalation anesthesia [ 28 ]. Propofol plus low-dose fentanyl sedation is commonly used in short-term outpatient surgery, such as gastrointestinal endoscopy and induced abortion.…”
Section: Discussionmentioning
confidence: 99%